Effects of source and rates of calcium application on growth, quality and anthracnose control in papaya (Carica papaya L.) - Madani, Babak (2014)
Papaya (Carica papaya L.) is the third most important fruit after durian and banana in Malaysia. ‘Eksotika II’, a high yielding F1 hybrid, is a well-liked papaya cultivar in Malaysia for its good quality. Although, ‘Eksotika II’ has gained much popularity in the domestic and export markets, the harvested fruits are susceptible to anthracnose infection that limits its acceptability. Calcium plays a key role in enhancing plant growth and increasing fruit quality and storage life. It could be used as an alternative to fungicides to reduce disease incidence and hence to increase postharvest quality. So far, little attention has been paid to investigate the effect of calcium pre-harvest application on post-harvest quality of papaya, especially with respect to‘Eksotika II’ papaya. Four experiments were conducted in Agro technology Unit, University Agriculture Park, Universiti Putra Malaysia, Serdang, Selangor during 2011-2013 in order to evaluate the effect of pre-harvest calcium application on plant growth, fruit calcium content, post-harvest quality, anthracnose disease incidence and some enzymatic activities in papaya fruits. In the first experiment, papaya seedlings were established in pots and irrigated with a standard nutrient solution in a net house. Papaya plants were sprayed with three different sources of calcium (calcium chloride, calcium nitrate and calcium propionate) at four different concentrations (0, 60, 120 and 180 mg L-1). Results showed that calcium content in leaves of plants was not affected significantly by the different sources of calcium. However, increased calcium concentrations applied to the leaves enhanced calcium concentration in papaya leaves. In addition, increased concentrations of calcium enhanced stem height and diameter. Another experiment was carried out to find out the suitable source of calcium for better post-harvest qualities of papaya in the field. Different concentrations of calcium (0, 34, 67, 100 mM) in the form of calcium chloride and calcium nitrate were sprayed at 21 days after flower anthesis to the fruits and leaves. Spray applications were repeated every two weeks for six times. Results revealed that calcium content in fruit peel and pulp was higher for calcium chloride compared to calcium nitrate. Also, calcium chloride caused significantly smaller lesion diameter compared with those found in plants treated with calcium nitrate. Increased calcium concentration decreased ethylene production and increased ascorbic acid content in fruits. Thus, calcium chloride was found better as a calcium source for increasing calcium content in fruits and decreasing anthracnose lesion diameter. In the third experiment, various concentrations of calcium chloride (0, 0.5, 1.0, 1.5 and 2.0%) were sprayed to different sites of papaya (leaves, fruits, leaves plus fruits). Fruits of uniform size and shape were harvested at index 2 and stored at 12± 2oC and 85-90% relative humidity. Fruit samples for each treatment were used for measurement 21 days after storage. It was found that there were considerable increases in peel and pulp calcium content, firmness, titratable acidity, ascorbic acid storage life and overall quality of fruits when calcium was applied in fruits and fruits plus leaves compared to calcium application in leaves only. In addition, ethylene production, respiration rate, soluble solids concentrations, disease incidence, and disease severity were considerably lower in fruits when calcium was applied in fruits and fruits plus leaves compared to calcium application in leaves only. In the fourth experiment, 0, 1.5 and 2% calcium chloride was sprayed in leaves plus fruits. Results showed that polygalacturonase (PG) and pectin methyl esterase (PME) activities decreased with increasing calcium concentrations. Microscopy images confirmed that cell wall structures of fruit peel and pulp were preserved more in the middle lamella of calcium chloride-treated fruits compared to control. Also, results indicated that at 1.5% calcium chloride respiration rate, ethylene production, soluble solids concentrations, disease incidence and severity significantly decreased compared with control. In contrast, at 1.5% calcium chloride ascorbic acid, titratable acidity, firmness, storage life and overall quality markedly increased compared with control. Therefore, spraying with 1.5% calcium chloride to the leaves and fruits is suitable for better post-tharvest quality, higher calcium content in fruits and lower anthracnose disease in papaya.